Children with developmental disabilities and sleep problems: Parental beliefs and treatment acceptability - Keenan, R; Wild, MR; McArthur, I; Espie, C (2007)
Background: This exploratory study investigated the relationships between illness beliefs and treatment acceptability among parents of children with a developmental disability living at home who had sleep onset or maintenance problems. Materials and Methods: A within-subject correlational design was employed. The parents of 58 children each completed questionnaires assessing their beliefs and attributions towards the sleep problem and the acceptability of two common treatments (behavioural and melatonin). Results: Parents believed sleep problems to be chronic, to have negative consequences, yet to be potentially curable/controllable. They rated behavioural treatment and melatonin similarly in terms of acceptability. Behavioural treatment acceptability was related to how long parents believed the sleep problem would last and to a number of causal attributions. The acceptability of melatonin was related to how severe the consequences of the sleep problem were believed to be and to a specific causal attribution. Parents who preferred melatonin to behavioural treatment believed that their child's sleep problem had more negative consequences on their child's life. Conclusions: Specific beliefs held by parents about their child's sleep problems might influence treatment acceptability and treatment choice. Parents are split between those who would prefer behavioural treatment and those who would prefer melatonin. However, as the sleep problem becomes more severe, it seems more likely that parents would choose the pharmacological treatment. © 2007 The Authors.